(untitled) (Eurasian Journal of Philology Science and Education, 2019)
This articlet is about a technique of writing of the essay on the basis of the new technology of outstanding person of the Kazakh pedagogics K.O. Bitibayeva. The technique of writing of the essay in detail is analyzed and considered on the agenda of the modern school program. K. Bitibayeva’s technology «Oi tastay, oilanu» represents a model of pedagogical experience of the author which purpose is awakening of informative and creative abilities and research competences of pupils. It is confirmed, proceeding from own experience, on the example of texts of the epic of M. Auezov «the Way of Abay», the developing interest, motivation and cogitative activity of pupils.